Student response to teaching of memory cues and resumption strategies in computer science classes - John, Noah, author; Ruiz, Jaime, advisor; Böhm, Wim, committee member; DeLosh, Ed, committee member (Colorado State University. Libraries, 2015)
Programming is a creative process that requires the ability to concentrate and juggle multiple concepts simultaneously in one's mind. Existing research shows there is a tangible cost when a programmer is interrupted as the programmer must recover the context of his work and refocus on the task at hand. However, computer science (CS) students are rarely taught about interruptions and how to manage them. Instead, teaching tends to focus only on technical concepts. In addition, there is little research on interruptions with respect to CS students. Therefore, our research examines what happens when CS students are taught about interruptions and how to cope with them. The objective of this research is to determine if CS students are affected by interruptions, what knowledge CS students possess regarding memory cues and resumption strategies, and what their opinion is of this material. To answer these questions, we began by conducting a pilot study with fifteen students that consisted of an initial questionnaire, a seminar on memory cues and resumption strategies, and a follow-up questionnaire. After positive findings, we conducted a user study with approximately two-hundred undergraduate CS students. Our user study was comprised of a modified initial questionnaire, an identical seminar on memory cues and resumption strategies, and a modified follow-up questionnaire. Our results demonstrate that CS students are affected by interruptions, but 73% of students report not knowing methods to mitigate them. After learning about memory cues and resumption strategies, students report that the material is useful and that they want to study it. Their most significant feedback is that they have a strong desire to include these techniques in CS curriculums, reporting a mean score of 7.78 out of 10, where 0 signifies strong disagreement and 10 signifies strong agreement.
Keywords: memory cues; task resumption; interruptions; teaching; students